Exploring the Maritime Words: An Introduction - I Wayan Dirgayasa (English Language Teaching and Research, 2018)
Maritime English is also known as sea words or sea speak. It is the language used in a maritime world or maritime industry worldwide. As its name, the Maritime English (ME) is the most typical and unique language among other branches of the English for Specific Purposes (ESP) such as English for business (EB), English for Tourism (ET), English for Journalism (EJ), etc.  This paper attempts to explore an overview of the nature of Maritime English in terms of spelling, grammatical patterns, and vocabulary usage. Keywords: Spelling, grammatical patterns, vocabulary usages